EDMODO AS A VIRTUAL LEARNING ENVIRONMENT IN ACADEMIC WRITING CLASS - Yustinus Calvin Gai Mali (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
Minister of Education and Culture Republic of Indonesia, through its substantial policy stipulated in Indonesian Qualification Framework (KKNI), has issued integrating technology into teachers' pedagogical practices. Responding creatively to the policy, the study explores 21 Indonesian undergraduates' perspectives on the use of Edmodo, a virtual learning environment as rvell as a pedagogical and collaborative communication system, in facilitating them to achieve the learning objectives in Academic Writing Class at English Language Education Study Program, Satya Wacana Christian University (ED-SWCU). Data were collected through an online questionnaire and interview. On the questionnaire, the participants responded 18 multiple-choice statements and 2 open-ended questions dealing with possible advantages and challenges in using Edmodo. In the interview process, the researcher involved 4 pafticipants to explore their perspectives on how Edmodo facilitates them to achieve learning objectives in their classroom. The data analysis provides some evidence that the students respond positively the use of Edmodo. Further, with regard to the findings, the study would seem to indicate the essence of teacher-student communication and the teacher's feedback in helping the students achieve the leaming objectives. Eventually, the study hopes to provide ED-SWCU students, regarded as an English teacher candidate, and Indonesian teachers with insights into the pedagogical applications ofusing Edmodo. It is expected that they can have more alternatives on conceivable educational technologies they can utilize to support their teaching activities and to facilitate their students achieve particular learning objectives in their classrooms.